Identities for Harmonic Numbers and Binomial Relations Via Legendre Polynomials - Tuladhar, B. M.; López-Bonilla, J.; López-Vázquez, R. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
We employ the orthonormality of the Legendre polynomials to deduce binomial identities. The harmonic numbers Hn are connected with the derivatives of binomial coefficients, this fact allows to deduce identities involving the Hn.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 2, 2017, page: 92-97